PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN KONSUMEN PADA TOKO ONLINE - Rika Lili Wati (Program Studi Ilmu Administrasi Bisnis, FIABIKOM, Unika Atma Jaya, 2018)
One strategy to satisfy consumers is through the services provided. Qualified service if theservice can meet customer expectations so that consumers become satisfied. The purpose ofthis study is to determine whether there is influence of service quality to customer satisfactionat Zalora Indonesia online store. Variable service quality is measured using sevendimensions, namely efficiency, reliability, guarantee, privacy, responsiveness, compensationand contact. And consumer satisfaction variable is measured using two dimension that is atcheck-out customer satisfaction and after delivery customer satisfaction. The number ofrespondents is 100 people with purposive sampling method. Based on the results ofcorrelation and simple linear regression analysis showed that there is influence of servicequality to customer satisfaction at Zalora Indonesia online store with strong relationshiplevel. While based on the results mean score and overall mean score shows that efficiencyhas the highest value of 4,37 compared to other dimensions.